Investigating Efficacy of Cu Nano‐Particles as Additive for Bio‐Lubricants. Issue 1 (18th December 2017) - Garg, Pooja; Kumar, Ajay; Thakre, G. D.; Arya, P. K.; Jain, A. K.
Abstract : Use of nano‐materials as lubricant additives is gaining tremendous importance due to their capabilities in enhancing the tribo‐performance. The nano‐particles of various elements and compounds are efficiently blended in mineral base oils enhancing their physico‐chemical as well as tribological properties. However, in recent times due to the environmental concerns, focus is being shifted toward bio based lubricants. Bio lubricants are obtained from plant oil by various chemical modification techniques. They are environment friendly, biodegradable and have better lubricating properties than the mineral oil based counterparts. The major challenge however for these lubricants is the selection of appropriate additives. The commercial additives developed for mineral base oils are generally toxic and not suitable for the Biolubricants. In this context, the present paper attempts to investigate the efficacy of Cu nano‐particles as additive for Biolubricants. The non‐edible karanja oil has been chemically modified to karanja ester and used as biolubricant. The functionalized Cu nano‐particles have been blended in various concentrations in biolubricant and the tribological performance investigated using four ball tribo‐tester. In order to ascertain the efficacy of Cu nano‐particles as additives, the tribo‐performance of Cu nano‐particle blended biolubricant has been compared with that of Zinc dialkyl dithio phosphate (ZDDP) blended biolubricant in equal concentrations. ZDDP is a conventional commercially available multi‐purpose additive that enhances the tribo‐performance of lubricating oils. The comparative study of experimental results showed that ZDDP helps in enhancing the anti‐wear performance of bio‐lubricant while the Cu nano‐particles aided in enhancement of anti‐friction behavior of biolubricant.